Pharmacist-led intervention in treatment non-adherence and associated direct costs of management among ambulatory patients with type 2 diabetes in southwestern Nigeria - Aduke E. Ipingbemi; Wilson O. Erhun; Rasaq Adisa (BMC, 2021)
Abstract Background Non-adherence to recommended therapy remains a challenge to achieving optimal clinical outcome with resultant economic implications. Objective To evaluate the effect of a pharmacist-led intervention on treatment non-adherence and direct costs of management among patients with type 2 diabetes (T2D). Method A quasi-experimental study among 201-patients with T2D recruited from two-tertiary healthcare facilities in southwestern Nigeria using semi-structured interview. Patients were assigned into control (HbA1c < 7%, n = 95) and intervention (HbA1c ≥ 7%, n = 106) groups. Baseline questionnaire comprised modified 4-item Medication Adherence Questions (MAQ), Perceived Dietary Adherence Questionnaire (PDAQ) and International Physical Activity Questionnaire, to assess participants' adherence to medications, diet and physical activity, respectively. Post-baseline, participants were followed-up for 6-month with patient-specific educational intervention provided to resolve adherence discrepancies in the intervention group only, while control group continued to receive usual care. Subsequently, direct costs of management for 6-month pre-baseline and 6-month post-baseline were estimated for both groups. Data were summarized using descriptive statistics. Chi-square, McNemar and paired t-test were used to evaluate categorical and continuous variables at p < 0.05. Results Mean age was 62.9 ± 11.6 years, and 160(79.6%) were females. Glycated haemoglobin (HbA1c) was 6.1 ± 0.6% (baseline) and 6.1 ± 0.8% at 6-month post-baseline (p = 0.094) for control group, and 8.7 ± 1.5% (baseline) versus 7.8 ± 2.0% (6-month), p < 0.001, for the intervention. Post-baseline, response to MAQ items 1 (p = 0.017) and 2 (p < 0.001) improved significantly for the intervention. PDAQ score increased significantly from 51.8 ± 8.8 at baseline to 56.5 ± 3.9 at 6-month (p < 0.001) for intervention, and from 56.3 ± 4.0 to 56.5 ± 3.9 (p = 0.094) for the control group. Physical activity increased from 775.2 ± 700.5 Metabolic Equivalent Task (MET) to 829.3 ± 695.5MET(p < 0.001) and from 901.4 ± 743.5MET to 911.7 ± 752.6MET (p = 0.327) for intervention and control groups, respectively. Direct costs of management per patient increased from USD 327.3 ± 114.4 to USD 333.0 ± 118.4 (p = 0.449) for the intervention, while it decreased from USD 290.1 ± 116.97 to USD289.1 ± 120.0 (p = 0.89) for control group, at baseline and 6-month post-baseline, respectively. Conclusion Pharmacist-led intervention enhanced adherence to recommended medications, diet and physical activity among the intervention patients, with a corresponding significant improvement in glycaemic outcome and an insignificant increase in direct costs of management. There is a need for active engagement of pharmacists in management of patients with diabetes in clinical practice. Trial registration ClinicalTrials.gov identifier: NCT04712916 . Retrospectively-registered.